Queer Kinship : Race, Sex, Belonging, Form - Freeman, Elizabeth, 1966-; Bradway, Tyler, 1983- (Book collections on Project MUSE., 2022)
"Queer Kinship gathers essays written at the intersection of queer theory and kinship theory. While both queer scholars and anthropologists have written accounts of kinship independently, this volume brings together interdisciplinary work from the two fields to consider what queer kinship looks like after marriage equality and in the wake of the 2016 election, and with attention to the centrality of indigeneity, Blackness, race, and colonialism to queer kinship studies. Combining the material interests of the social sciences with queer theory's investment in performance, signification, and the history of sexuality, the essays in this volume push the methodological and theoretical underpinnings of queer theory forward"--